Mean-field model of jet formation in a collapsing Bose-Einstein condensate - Adhikari, Sadhan K. [UNESP] (IOP Publishing, 2004)
We perform a systematic numerical study, based on the time-dependent Gross-Pitaevskii equation, of jet formation in collapsing and exploding Bose-Einstein condensates as in the experiment by Donley et al (2001 Nature 412 295). In the actual experiment, via a Feshbach resonance, the scattering length of atomic interaction was suddenly changed from positive to negative on a pre-formed condensate. Consequently, the condensate collapsed and ejected atoms via explosion. On disruption of the collapse by suddenly changing the scattering length to zero, a radial jet of atoms was formed in the experiment. We present a satisfactory account of jet formation under the experimental conditions and also make predictions beyond experimental conditions which can be verified in future experiments.
Keywords: Atomic scattering; Bose-Einstein condensates; Jet formation; Computer simulation; Magnetic field effects; Mathematical models; Quantum theory; High energy physics